Systematic Literature Review: Analisis Kebutuhan Instrumen Asessmen untuk Mengukur Kemampuan Coding dan Computational Thinking Pada Mahasiswa Pendidikan Fisika - Berlianti Mandasari; Sardianto Markos Siahaan; Muhamad Yusup (Postgraduate, University of Mataram, 2026)
This study aims to analyze the need for developing assessment instruments to measure coding skills and Computational Thinking (CT) among physics education students through a Systematic Literature Review (SLR). The literature search was conducted through Scopus and Google Scholar databases using systematic filtering procedures following PRISMA guidelines. The inclusion criteria covered studies addressing coding and/or CT in educational contexts, focusing on assessment instruments, providing full-text access, employing clear research methods, and published between 2022 and May 2026. The selection process identified 13422 initial articles, of which only 14 met all inclusion criteria. The findings reveal that studies specifically focusing on assessment instruments for coding and CT are still limited compared with research emphasizing instructional implementation. Most studies focus on Computational Thinking (9 studies), while only 2 studies discuss coding skills, and 3 studies indirectly examine both aspects. Based on educational levels, the studies are distributed across early childhood education (3), primary education (3), secondary education (1), higher education (2), and non-specific contexts (5). These findings indicate that research at the higher education level, particularly related to physics education, remains limited. Furthermore, no standardized instrument has yet been consistently applied to assess these competencies. However, recent developments in project-based assessment, STEM integration, and digital technology utilization demonstrate promising opportunities for more authentic assessment approaches. Therefore, this study highlights the importance of developing structured, valid, and reliable assessment instruments that not only evaluate learning outcomes but also capture students’ thinking processes during learning activities.